Learning Model of The Yellow Book In Improving Maharah Qiro'ah At The Zainul Mu'in Islamic Boarding School - azizah, nur; Bin Madi, Faisol Nasar; Irawan, Bambang (Universitas Cokroaminoto Palopo, 2025)
This research aims to uncover the mystery of the success of the yellow book learning model program in increasing maharah qiro'ah at the Zainul Mu'in Islamic Boarding School Kalisat-Jember with sub-focus: (1) Implementation of the Yellow Book Learning Model in improving Maharoh Qiro'ah. (2) Problems with the Yellow Book Learning Model in Increasing Maharoh Qiro'ah. This research uses a qualitative approach with a case study design which includes in-depth and contextual analysis using three data collection techniques, namely; interviews, observations and documentation. Which includes caregivers, teacher council, students at the Zainul Mu'in Islamic Boarding School. The data obtained from the research is then analyzed to suit the research objectives and presented in the form of a description. The research results have found (1) Implementation of the Yellow Book Learning Model in Improving Maharoh Qiro'ah, including two learning models, namely: Bandungan/Wethonan, Sorogan; These two learning models are very helpful for the success of Maharoh Qiro'ah and the success of the goals desired by caregivers and the teacher council. (2) Problems with the Yellow Book Learning Model in Improving Maharoh Qiro'ah, based on two factors, namely: Linguistic and Non-Linguistic, the two problems mentioned above are used as evaluation material at the Zainul Mu'in Islamic Boarding School. Apart from that, two solutions were found, namely: Emotional Approach and Individual Approach.